2012
DOI: 10.12816/0003147
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Hemcon Dental Dressing Versus Conventional Method of Haemostasis in 40 Patients on Oral Antiplatelet Drugs

Abstract: abstract:Objectives: The purpose of the study was to evaluate the effectiveness of the HemCon Dental Dressing (HDD) in controlling post extraction bleeding and to ascertain its role in healing of extraction wounds, as compared to control. Methods: The 40 participants in the study were all receiving oral antiplatelet therapy (OAT). A total of 80 extractions were conducted without altering the patients' drug therapy. The extraction sites were divided into 2 groups: one group received a HDD, and the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
(20 reference statements)
0
26
0
3
Order By: Relevance
“…21,22 Comparing the results of this study with our previous study on HemCon Dental Dressing (HDD), the mean time taken to achieve hemostasis is significantly lower when ADD (73 seconds) or HDD (53 seconds) was used compared with conventional method. 4 Increase in the time to achieve hemostasis using ADD is attributed to the fact that the patients with INR up to 3.5 were included in this study in contrast to our previous study on Hemcon dressing where INR limit was 3. On comparing the results of postoperative healing and pain between ADD and Hemcon dressing, both showed similar potential of superior healing and minimal postextraction pain and complications.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…21,22 Comparing the results of this study with our previous study on HemCon Dental Dressing (HDD), the mean time taken to achieve hemostasis is significantly lower when ADD (73 seconds) or HDD (53 seconds) was used compared with conventional method. 4 Increase in the time to achieve hemostasis using ADD is attributed to the fact that the patients with INR up to 3.5 were included in this study in contrast to our previous study on Hemcon dressing where INR limit was 3. On comparing the results of postoperative healing and pain between ADD and Hemcon dressing, both showed similar potential of superior healing and minimal postextraction pain and complications.…”
Section: Discussionmentioning
confidence: 89%
“…On comparing the results of this study with our previous study on HDD, Axiostat Dental Dressing is found to be as effective and at par in achieving hemostasis in patients on oral antiplatelet therapy. 4 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall evaluation of all the above-mentioned parameters for each site allowed definition of the type of healing, as better, worse, or equal compared with the control site (Table I). 21 Any postoperative complications were noted in the clinical record.…”
Section: Procedures Parametersmentioning
confidence: 99%
“…7,[15][16][17][18][19] A new adhesive agent, HemCon Dental Dressing (HDD) (Zimmer Holdings, HemCon Medical Technologies, Inc., Beaverton, OR), has been recently introduced into oral surgery and already used for tooth extractions in patients taking antithrombotic drugs. 20,21 It derives from the agent used by the U.S. forces during the wars in Iraq and Afghanistan, which is based on chitosan, a natural biocompatible polysaccharide extracted from the shell of crustaceans. It has proven ability to quickly seal the wound, stabilizing the clot and protecting the mucosa during the healing period, and has an efficient antimicrobial activity against many bacterial species.…”
mentioning
confidence: 99%